PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DAN KINERJA GURU MILITER RESIMEN INDUK KOMANDO DAERAH MILITER VII/WIRABUANA DI SULAWESI - Muhammad Yusuf (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
The aims of this research are: (1) to test influence leadership style to satisfaction (2) to analyze the effect of organization culture to job satisfaction (3) to analyze the effect of ledership style to ferformance (4) to analyze the effect of organization style to performance (5) to analyze the effect of job satisfaction to performance. The Research used primary data tougth a survey on 131 teacher is samples taken from the total 194 teacher who already had minimum one year of service as military teacher per December 2014, The research was done from April to December 2015. Structural Equation Modeling (SEM) by used to analyze this data. The results of the research show that: 1) Leadership style had positive direct and significant effect to satisfaction 2) organization culture had positive direct and significant effect job satisfaction 3) leadership style had negative effect to performance 4) organization culture had negative effect to performance 5) job satisfaction had positive direct and significant effect to performance.